Pengembangan E-Komik Pembelajaran pada Materi Gas Karbon di Sekitarku di Kelas IV Sekolah Dasar - Virna Dwi Agustin; Isna Ida Mardiyana (Mataram University, 2026)
This development research aimed to produce an educational e-comic learning medium on the topic “Carbon Gases Around Me” for fourth-grade elementary school students and to determine its validity, attractiveness, and effectiveness. This study employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the trial were 23 fourth-grade students of Elementary School of Kemayoran 2, Bangkalan Regency. The results showed that the developed educational e-comic learning medium met the criteria of being valid based on expert validation, highly attractive according to teacher and student responses, and effective in supporting the learning process. In addition, students achieved classical learning mastery after using the learning medium. These findings indicate that the educational e-comic learning medium is feasible and effective for supporting science learning in elementary schools.